Determination of Band Structure at GaAs/4H-SiC Heterojunctions. (24th August 2016) - Liang, Jianbo; Shimizu, Sae; Arai, Manabu; Shigekawa, Naoteru
Abstract : The effects of thermal annealing process on the interface in p + -GaAs/n-SiC heterojunctions fabricated by using surface-activated bonding (SAB) were investigated. It was found by measuring their current-voltage ( I-V ) characteristics that the reverse-bias current and the ideality factor were extracted to be 7.57 ´ 10 -7 A/cm 2 and 1.33, respectively, for the junctions annealed at 400 °C. The flat-band voltage obtained from capacitance-voltage ( C-V ) measurements was found to be 1.29 eV, which is almost consistent with the turn-on voltage extracted from I-V characteristics. These results suggest that the SAB-based GaAs/SiC heterojunctions are applicable for fabricating high-frequency power devices.